The Ideational Unity of Literary Text from the Psycholinguistic Perspective - Dyachuk, Nataliya (East European Journal of Psycholinguistics, 2015)
The article focuses on the ideational unity analysis of the literary text. The ideational unity is viewed through the main psycholinguistic features of the literary text: integrity and coherence. The original text and three target versions were analyzed. The Smile by R. Bradbury and its Ukrainian versions made by professional translators Lada Kolomiyets, Andriy Yevsa, Yaroslav Vepryniak were the principal sources of the analysis. The empirical research results of the ideational  unity of the literary texts were given in the article. The description of the research methods used for integrity and coherence analysis in the chosen literary texts was represented. The figurative analysis of the ideational unity existence in literary text was given in the article.ReferencesNussbaumer, A. (1994). Studienbuch Linguistik. Tübingen: NiemeyerZavhorodnia, L (2009). Textoznavstvo [Text Studies]. Cherkasy: Brama-UkrainaZimnyaya, I. (2001). Lingvopsichologiya Rechevoy Deyatelnosti [Linguopsychology ofSpeech Activity]. Voronezh: Modek.Yakhibbaeva, L (2008). Kategorii tselnosti / tselostnosti i svyaznosti kak osnovnyepriznaki teksta [Categories of Integrity and Coherence as the Basic Features of a Text].Lingvokulturologia, 2, 209–214.Leontyev, A. (2005). Psikholingvistichiskie edinitsi i porozhdenie rechevogovuskazuvaniya [Psycholinguistic Units and Speech Utterance Production]. Moscow: EditorialURSS.Moskalskaya, O. (1981). Grammatika Teksta [Text Grammar]. Moscow: VysshayaShkola.Novikov, A. (2003). Tekst i «kontrtekst»: dve storony protsessa ponimaniya. Journal ofPsycholinguistics, 1, 64–76.Sorokin, Yu. (1985). Psicholingvisticheskie Aspekty Izucheniya Teksta [PsycholinguisticAspects of Studying Text]. Moscow: Nauka.Stepanova, M. (2008). Kogeziya i kogerentnost v britanskom mediadiskurse. Philologiya,333–335.SourcesBradbury R. (1983) Fahrenheit. Short Stories. Moscow: Raduga Publishers.Bradbury, R. The Smile. Retrieved from http://raybradbury.ru/library/story/52/9/1/.Bradbury, R. (1999a). Ousmishka [The Smile]. transl. by L. Kolomiyets. VsesvitniaLiteratura v Serednikh Navchalnykh Zakladakh Ukrainy, 3(227), 11–12. Кyiv: PedahohichnaPresa,.Bradbury, R. (1999b). Ousmishka [The Smile]. transl. by Yaroslav Vepryniak.Zarubizhna Literatura. 6th Form. Textbook. 296–300. Ternopil’: Navchal’na Knyha–Bohdan.Bradbury, R. (2011). Ousmishka [The Smile]. transl. by Andriy Yevsa. SvitovaLiteratura. 6th Form. Textbook, 374–381. Kharkiv: FOP Spivak.